Design of self-assembled micelles based on natural dual-targeting strategies and evaluation of their anti-liver cancer effects as drug delivery systems - Binbin Wang; Bai Lv; Hao Li; Jie Zhang; Yaning Ding; Jianwen Zhou; Ming Bu; Li Fan; Cuiyan Han (npj Precision Oncology)
Abstract Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world and in China, Most patients are already in an advanced stage at the time of diagnosis, and the chance of complete surgical resection is lost, therefore, drug treatment is particularly important. Angelica sinensis polysaccharide (ASP) has natural liver-targeting properties, berberine (BBR) is a lipophilic cation with anticancer activities and mitochondrial-targeting properties, and honokiol (HNK) has mitochondria-dependent anticancer effects against cancer. Therefore, the aim of the present work was to synthesize Angelica sinensis polysaccharide-berberineamphiphilic polymer (ASP-SS-BBR) loaded with HNK to prepare the micelles ASP-BBR-PM@HNK to improve the hepatic targeting ability of the nanoparticles and the mitochondrial targeting ability in HCC cells and to enhance the anti-HCC effect of HNK. The findings of this study demonstrate the successful synthesis of ASP-BBR-PM@HNK, characterized by a particle size of 48.6 ± 1.13 nm. The formulation exhibits commendable stability, a sustained-release profile, and the capability for glutathione (GSH)-responsive release. ASP-BBR-PM@HNK is efficiently internalized by HepG2 cells, exhibiting the highest rate of cell inhibition. Additionally, the use of Gal and Man as receptor blockers confirmed the formulation’s superior targeting capabilities, including exceptional mitochondrial targeting. Subsequent in vivo experiments employing BALB/c nude mice as a model further corroborated these experimental outcomes. This research has successfully developed an effective natural dual-targeting system, offering a novel approach for the precise treatment of liver cancer.